PENTINGNYA KESEHATAN OLAHRAGA DALAM MENINGKATKAN KEBUGARAN DAN PRESTASI ATLET - Nimrot manalu; Cristovelsaragih; Felix Adriano Tarigan; Ferdi Hasan Lubis; Muhammad Hafiz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sports health is a fundamental aspect that plays a key role in the development of an athlete's physical abilities and achievement. This article aims to outline the vital role of sports health in improving physical fitness levels and analyze its impact on performance outcomes during competitions. The method used is a literature review, reviewing various scientific literature sources, sports theory, and relevant training guidelines. The results of the discussion indicate that the application of sports health principles—which include injury prevention, physical recovery, balanced nutrition, and mental health—plays a significant role in optimizing organ function, increasing endurance, and maintaining a balanced physical and mental state for athletes. Furthermore, sports health has been shown to minimize the risk of health problems, accelerate the recovery process, improve concentration, and ensure consistent performance. It is concluded that sports health is not merely a supplement, but a primary foundation that must be implemented continuously so that athletes can achieve maximum fitness and achieve outstanding performance safely and sustainably.